Hydrothermal treatment of gadolinium oxide in presence of silica - Simoneti, J. A. [UNESP]; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. [UNESP] (Taylor & Francis, 1994)
Hydrothermal and solvothermal (isopropanol) treatments of gadolinium oxide and silica were investigated under different pressure and temperature conditions. Products were examined by infrared vibrational spectroscopy (IR), x-ray powder diffraction (XRD) and thermal analysis (DTA, TG). Hexagonal gadolinium hydroxide was obtained in hydrothermal conditions, even in presence of silica, while no change was observed from isopropanolic medium treatment. Hydrothermally treated samples are more reactive as precursors for solid state reactions in inorganic synthesis.
Keywords: Gadolinium compounds; High pressure effects; High temperature effects; Oxides; Phase transitions; Silica; Single crystals; Spectroscopy; Thermal effects; Thermoanalysis; X ray powder diffraction; Gadolinium oxide; Hexagonal gadolinium hydroxide; Hydrothermal treatment; Infrared vibrational spectroscopy; Isopropanolic medium treatment; Solvothermal treatment; Heat treatment